The Effects of Anodal Transcranial Direct Current Stimulation on Sleep Time and Efficiency - McIntire, Lindsey K.; McKinley, R. Andy; Goodyear, Chuck; McIntire, John P. (Frontiers in Human Neuroscience, 2020)
A single session of anodal transcranial direct current stimulation (tDCS) has been shown to increase arousal in healthy participants for up to 24-hours post stimulation. However, little is known about the effects of tDCS on subsequent sleep in this population. Based on previous clinical studies, we hypothesized that anodal stimulation to the left dorsolateral prefrontal cortex (lDLPFC) would produce higher arousal with decreased sleep time and stimulation to the primary motor cortex (M1) would have the converse effect. Thirty-six active duty military were randomized into one of three groups (n=12/group); active anodal tDCS over the lDLPFC, active anodal tDCS over M1, or sham tDCS. Participants answered questionnaires 3 times a day and wore a wrist activity monitor (WAM) to measure sleep time and effeciency for 3 weeks. On weeks 2 and 3 (order counterbalance), participants received stimulation at 1800 hours before 26-hours of sustained wakefulness testing (sleep deprived) and at 1800 hours without sleep deprivation (non-sleep deprived). There were no significant effects for the non-sleep deprived portion of testing. For the sleep deprived portion of testing, there were main effects of group and night on sleep time. The DLPFC group slept less than the other groups on the second and third night following stimulation. There is no negative effect on mood or sleep quality from a single dose of tDCS when participants have normal sleep patterns (i.e., non-sleep deprived portion of testing). The results suggest that stimulation may result in faster recovery from fatigue caused by acute periods of sleep deprivation, as their recovery sleep periods were less.